2012
DOI: 10.1080/15222055.2012.676008
|View full text |Cite
|
Sign up to set email alerts
|

Partial Replacement of Fishmeal with Soybean Meal and Soy Protein Concentrate in Diets of Atlantic Cod

Abstract: Juvenile Atlantic cod Gadus morhua (initial weight = 24.1 ± 1.4 g [mean ± SE) were fed diets in which fish meal (FM) was replaced with soy protein concentrate (SPC) and soybean meal (SBM) in isonitrogenous, isocaloric diets for 84 d. A standard marine finfish diet (3 mm, 54% protein, 14% fat) was modified to produce four experimental diets in which 50% of FM was replaced with soy at 0:1, 1:1, or 1:2 ratios of SPC:SBM and 100% FM replacement with a 1:1 ratio of SPC:SBM. No differences in mortality or feed intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 32 publications
(49 reference statements)
0
26
0
Order By: Relevance
“…Colburn et al . () concluded that soy protein concentrate was applicable at 500 g kg −1 in diets for Atlantic cod (Gadus morhua L.) without causing enteritis in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Colburn et al . () concluded that soy protein concentrate was applicable at 500 g kg −1 in diets for Atlantic cod (Gadus morhua L.) without causing enteritis in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…An approximately 2-mm-wide section of the distal intestine was removed from each fish, fixed in 10 % buffered formalin, and stained with hematoxylin and eosin using standard histological techniques (Burrells et al 1999). Intestinal morphology was assessed using an ordinal scoring system based on lamina propria thickness and cellularity, submucosal connective tissue width, and the number of large vacuole, adapted from Knudsen et al (2007) and Colburn et al (2012) as described in Barnes et al (2014).…”
Section: Histological Analysismentioning
confidence: 99%
“…Intestinal morphology was assessed using an ordinal scoring system on lamina propria thickness and cellularity, submucosal connective tissue width, and the number of large vacuoles (Knudsen et al 2007;Colburn et al 2012). The ranking criteria are described in Table 4.…”
Section: Connective Tissue Between Base Of Folds and Stratum Compactummentioning
confidence: 99%
“…An approximately 2-mm-wide section of the distal intestine was Knudsen et al 2007;Colburn et al 2012). …”
mentioning
confidence: 99%